GLOBAL GOVERNANCE AND SUSTAINABLE DEVELOPMENT: THE CASE OF UN’S SUSTAINABLE DEVELOPMENT GOALS - Le, Kieu Phuong (International Journal of Application on Economics and Business, 2024)
The achievement of sustainable development, which is essential for preserving a healthy world for future generations, depends on the implementation of efficient global governance. Traditional, nation-state-focused approaches struggle to address difficulties that cross borders. In contrast, global governance structures facilitate collaboration by establishing frameworks—such as the Sustainable Development Goals established by the United Nations—and unite a wide range of actors—including businesses, governments, and nations—to exchange resources, expertise, and optimal methodologies. This collaborative effort is essential to tackle complex issues like climate change and poverty, ultimately paving the way for a more sustainable future. This paper will discuss the roles and responsibilities of significant actors contribute largely on sustainable development, focusing on the emerging trend of global governance in the international order. By taking the case of UN’s 17 Sustainable Development Goals, key problems for the public sector and private one will be identified and also provide some further suggestions in improving the implementation of sustainable development.